Measuring the Social Piety Index and Influential Factors: A Study of Bangka Barat Regency - yusmaliana, Desfa; Sabri, Fadillah; Vebrian, Rajab; Arrosyad , M. Iqbal; Saputra, Adi; Tohir, Muhamad (Pascasarjana IAIN Metro, 2024)
This study aims to measure the social piety index and identify influential factors related to social piety among the residents of Bangka Barat Regency. The enhancement of community social piety is crucial, aligning with the local government's mission to foster competitive and virtuous human resources. The research employed a survey method and cluster technique (cluster random sampling) for data collection. The social piety index was determined based on three variables: individual worship activities (X1), knowledge about social piety (X2), and attitudes/behaviors reflecting social piety (X3). The findings reveal a high level of individual worship activities (X1: 65.22), a significant understanding of social piety (X2: 77.19), and favorable attitudes/behaviors reflecting social piety (X3: 66.31) within the community. Active participation in recitation and involvement in religious organizations emerged as dominant factors shaping individual piety. Engagement in good governance and participation in conservation/restoration were identified as key factors influencing knowledge about social piety. Respect for differences and involvement in good governance play pivotal roles in shaping attitudes/behaviors associated with social piety.